Pemberdayaan Guru SD melalui Pelatihan Literasi Numerasi dan Pembuatan Alat Peraga Numerasi - Poewanto, Bobby; Arwadi, Fajar; Samad, Moh. Ardani (ADMA : Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2024)
The aim of this activity is to increase the capacity of numeracy teachers according to the literacy and numeracy competency framework for elementary school teachers. By improving numeracy skills, teachers are expected to have an impact on students, thereby producing a generation proficient in numeracy. The training participants in this activity were 7 SDI Bollangi 1 teachers. There were two main activities in this training, namely numeracy training which aimed to make teachers understand the importance of numeracy in everyday life, and the importance of numeracy being included as content in other lessons. The second main activity is training in making simple numeration teaching aids so that it can make it easier for students to understand numeracy so that it can be implemented in everyday life. The results obtained by the majority of participants felt that there had been great progress from this activity and that this activity was also in accordance with current competency needs.